ABOUT ONE WAY OF ORGANIZATION UNIFIED SYSTEM FOR REGISTRATION OF SPACE RAYS - Mukashev, К.М.; Stepanov, А.В.; Sadykov, Т.Х.; Argynova, А.Х.; Zhukov, В.В.; Umarov , Ф.Ф.; Iskakov, Б.А. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
At present, at the high-mountain scientific station for the study of the physics of cosmic rays, various, independently operating unique experimental installations are used. The article discusses the ways and methods of combining these installations into a single system, which includes networks of scintillation detectors of the "carpet" type for registration of the electron-photon component, ground and underground monitors for registration of neutron components, calorimeters, Cherenkov detectors, a scintillation spectrometer and a number of other subsystems. The newly created unified system for registering cosmic rays based on the achievements of modern technology and scientific thought will have a high resolution, with a common databank with synchronization in time of operation of separate, independently operating experimental installations. The solution to this problem will make it possible to perform a detailed analysis of the recorded events from a single position, to carry out complex calculations of the spatial distribution, mass composition, and also the energy structure of cosmic rays with a high degree of accuracy.